Dangers of outpatient nimodipine use after spontaneous subarachnoid hemorrhage in accordance with the Comprehensive Stroke Center guidelines. (June 2018) - Chen, Ching-Jen; Turnage, Cassie; Sokolowski, Jennifer D.; Kumar, Jeyan S.; Kalani, M. Yashar; Park, Min S.
Highlights: The benefits of complete 21-day course of nimodipine therapy in patients with subarachnoid hemorrhage are unclear. Optimal length of nimodipine therapy is unclear, especially in SAH patients with low cerebral vasospasm risk. Nimodipine in the outpatient setting can be dangerous, and close blood pressure monitoring is recommended. Abstract: Despite the adverse effects and unclear benefit of the complete 21-day course of nimodipine therapy, The Joint Commission mandates adherence to nimodipine treatment for 21 days after hemorrhage or after hospital discharge if discharged within 21 days for Comprehensive Stroke Center (CSC) certification. We hereby present a 67 year-old male patient with Hunt-Hess grade 2 and Fisher grade 3 non-aneurysmal spontaneous subarachnoid hemorrhage who was discharged with oral nimodipine as stipulated by the CSC guidelines, and subsequently developed symptomatic hypotension. This report underscores the danger of outpatient nimodipine use and questions the optimal length of nimodipine therapy, especially in patients with low risk of vasospasm. Future studies, including randomized controlled trials and cost-effectiveness studies, are necessary to clarify the benefit of 21-day nimodipine therapy compared to a shortened duration of nimodipine.